Functionally graded nickel–tungsten coating: electrodeposition, corrosion and wear behaviour. (2nd July 2016) - Allahyarzadeh, M. H.; Aliofkhazraei, M.; Sabour Rouhaghdam, A. R.; Torabinejad, V.
Abstract : Nickel–tungsten functionally graded (FG) coatings were developed by pulse electrodeposition. To make a FG structure, pulse parameters were selected in eight layers with the tungsten content increasing along the thickness. The gradual increase in tungsten content to the surface will increase wear resistance and reduce the risk of cracking at the substrate. To investigate the microstructure and cross-section of Ni–W coating scanning electron microscope and to measure the chemical composition of the coating the energy dispersive spectroscopy analysis was used. Electrochemical and pin-on-disk wear tests were performed to investigate corrosion resistance and wear behaviour of the coating, respectively. Results showed that with reduction of duty cycle or increasing of frequency along this eight-layer structure, the tungsten content increased upward the surface. Results showed the superior wear resistance of the coating as compared to that of pure nickel. Moreover, the coefficient of friction decreased from 0.74 to 0.49 by an increase in the sliding distance.